Fragmented but coherent: Lexical cohesion on a YouTube channel. (December 2021) - Tanskanen, Sanna-Kaisa
Highlights: Lexical cohesion on YouTube is multimodal, cross-modal and intertextual. Cohesive ties exist between the video and the comments as well as between the comments. A YouTube discussion may appear fragmented but still show dense cohesion. Qualitative and corpus methods reveal how fragmentation is a feature on the surface only. Abstract: This paper investigates the use and functions of lexical cohesion within and across modes as well as levels of interaction on a YouTube channel, arguing that lexical cohesion contributes to coherence by establishing links between the video, the comments and sources elsewhere on the internet in a cross-modal and intertextual manner. The analysis focuses on one video and its comments section, investigating the use of cohesion in maintaining coherence and unity across a lengthy YouTube interaction initiated by the video and continued in the comments. Cohesive ties are examined with regard to their functions in the process of meaning-making in this mediated and multimodal context. The results reveal that the use of cohesive ties is extensive within and across modes and levels of interaction. Chains of cohesion are created within the comments, with cross-modal links to the video. Despite the complex multimodality of YouTube and the fragmentation of the comments as many participants post short comments one after another, the YouTube interaction is shown to be coherent.